Air Quality Monitoring and Analysis in Tasikmalaya City - Nurcholis Salman; Fadhila Muhammad Libasut Taqwa; Alimuddin Alimuddin; Andri Arthono (Journal of Community Based Environmental Engineering and Management, 2023)
Within the national scope, based on Government Regulation no. 47 of 1997 concerning the National Spatial Plan, the City of Tasikmalaya which is included in the East Priangan Region is included in the mainstay area. Where Tasikmalaya City functions as a Regional Activity Center (PKW) city. One result is the increased volume of traffic in the area. One of the impacts of motor vehicle traffic activity is air pollution. Air pollution is defined as the contamination of the atmosphere by gases, liquids or by-products in such concentrations and periods that can harm human health/life, and or create discomfort. The method used in conducting the research was in the form of monitoring ambient air parameters which were carried out at 10 points, spread across community activity centers in Tasikmalaya City. Based on the research that has been done, it can be concluded that the parameters Sulfur Dioxide (SO2), Nitrogen Dioxide (NO2), Oxidants (O3), Dust (TSP), Ammonia (NH3) and Hydrogen Sulfide (H2S) at 10 the testing location still meets the required quality standards based on PP RI No. 41 of 1999. Meanwhile, the results of noise level measurements have exceeded the noise level quality standards, so that treatment is needed in the form of implementing sound emission rules and localizing industrial pollutant sources.